Miscegenation in the Province of Costa Rica: the Case of Esparza - Acuña León, María de los Ángeles (Cuadernos Inter.c.a.mbio sobre Centroamérica y el Caribe, 2022)
The city of Esparza, established in 1574, was the administrative headquarters of the area between the Tárcoles and Tempisque rivers. In this region lived Spaniards, indigenous, blacks, mestizos and mulattos. Our objective in this article is to analyze how the process of miscegenation developed in the 18th century and to determine how the population of mixed origin evolved and what was the specificity of inter-ethnic relations in this area. For this reason, are analyzed the variables of legitimacy, illegitimacy, endogamy and exogamy, based on the systematization and processing of the data obtained from the sources. Parish records, together with population counts and other judicial, economic and ecclesiastical documentation, constitute the main sources for this article. In this way, we want to contribute to the knowledge about the dynamics of miscegenation, in a specific population of the Province of Costa Rica.